TEKNIK PENGAMBILAN SAMPEL SEDERHANA DI KELAS/SEKOLAH DASAR - Putri Nursida Aini; Nurhaswinda; Septira, Difva; Nurjannah, Annisa; Dallilah , Balqis; Fadillah, Shella; Oktoviani, Sofia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Selecting an appropriate sample is a crucial step in ensuring the validity of educational research results, particularly at the elementary school level, this research aims to explain the implementation and effectiveness of the Simple Random Sampling technique in classroom-based research. The methods employed include a literature review and participatory observation of the use of the lottery technique to determine research subjects from a population of students with relatively homogeneous characteristics. The findings indicate that simple random sampling is well suited for application in elementary schools due to its procedural simplicity, high level of objectivity, and its ability to ensure that every student has an equal chance of being selected without any bias from the teacher.However, at the elementary school level, this study aims to illustrate the implementation.The study concludes that for novice researchers or teachers conducting Classroom Action Research (CAR), simple random sampling is the most practical option while still adhering to scientific research principles.